Prevalence and Predictors of Social Support Utilization among Cancer Patients Undergoing Treatment - Hunninghake, John; Dong, Fanglong; Hines, Robert B; Ablah, Elizabeth; Taylor, Sarah (Kansas Journal of Medicine, 2014)
Background. The purpose of this study was to quantify the prevalence of cancer patients utilizing social support services while undergoing treatment and to identify patient and clinical factors associated with utilization of such services. Methods. This was a cross-sectional study. Surveys were distributed to three cancer clinics at 11 locations in the greater Kansas City metropolitan area in 2010. Study inclusion criteria included being at least 18 years old and undergoing treatment for cancer at the time of survey completion. Results. A total of 465 oncology patients completed surveys. Two-thirds (67.5%, n = 314) were undergoing treatment for cancer and were included in the final analysis. More than half (63.7%, n = 198) were female, and the average age was 58.9 ± 13.3 years. More than one-third (37.4%, n = 117) reported using cancer-related social support services. Additionally, 22% (n = 69) reported not using support services but were interested in learning more about those services. Patients had increased odds of having used support services if they were female (OR = 2.67; 95% CI = 1.47, 4.82), were younger adults, or had stage I-III (OR = 2.67; 95% CI 1.32, 5.26) or stage IV cancer (OR = 2.3; 95% CI 1.14, 4.75) compared to those who did not know their cancer stage. Conclusions. More than one-third of patients reported using social support services. A substantial portion of participants reported not using support services but were interested in learning more about those services. Increasing social support service utilization might be especially important to explore for men, those who do not know their cancer stage, and older adults.